A Feasibility and Acceptability Assessment of Photo-experiencing and Reflective Listening (PEARL): An Intervention to Promote Recovery Engagement After Gender-Based Harm - Sinko, Laura (Violence against women, 2024)
Photo-experiencing and Reflective Listening (PEARL) is a trauma-informed intervention developed to promote recovery engagement in survivors of gender-based violence (GBV). This study aimed to understand the feasibility and acceptability of PEARL and identify potential healing elements. GBV survivors were recruited in Philadelphia through an online survey (n = 20). Participants completed the PEARL intervention, a postintervention survey, and a follow-up interview. Results revealed PEARL to be both feasible and acceptable, with thematic analysis revealing its ability to facilitate purposeful reflection, connection to the present, and progress toward healing goals. PEARL shows promise as an engaging strategy to promote healing for survivors of GBV.